Development of Qualitative Meanings of Relative Adjectives denoting Materials - Y. Mao (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The features of active in the modern Russian language process of transition of relative adjectives in the category of qualitative are discussed. The process of development of qualitative meanings of relative adjectives denoting attribute through relation to various materials, substances is investigated. The purpose of the study is to identify the semantic and cognitive patterns of such a transition. The classification are presented of (1) relative adjectives with the meaning of material, developing qualitative semantics, (2) semantic patterns of development by these adjectives of qualitative meanings. It is shown that the derived adjectives are either characteristics of the surrounding world (leader of the thematic subgroup “visual sense”), or subjective characteristics (primarily the appearance and inner world of man). The evaluation, which develops by the original adjectives with qualitative meanings, and cultural and national conditioning of such meanings are described. To demonstrate the different perception of certain materials and their properties in different cultures a comparative linguistic material is given that is associated with qualitative adjectives in Russian and Chinese languages. The formal attributes of quality, appearing in adjectives, indicating relation to different materials and developing qualitative meaning, are examined: the possibility of formation of adverbs from adjectives and nouns.